Novas linhagens de Saccharomyces cerevisiae e híbridos entre S. cerevisiae e Saccharomyces kudriavzevii para a produção de cerveja, cachaça e vinho - Thelma Tirone Silvério Matos (2021)
Beer, wine and cachaça are beverages produced by fermentation and are appreciated worldwide. Routinely, producers and consumers are looking for new products that have better fermentation and sensory characteristics. From this perspective, the present work searched for strains of Saccharomyces cerevisiae isolated from spontaneous fermentation of cachaça to be used in beer production also made hybrids obtained between the strains obtained from the fermentation of cachaça and Saccharomyces kudriavzevii (used in fermentation of wine). The search for brewing strains in the production of cachaça resulted in obtaining three strains of S. cerevisiae capable of fermenting at temperatures of 10 and 20°C, producing low concentrations of H2S, fermenting maltose and maltotrise and withstanding stressful variations of the beer production process, in addition to having a neutral sensory characteristic. Therefore, the spontaneous fermentation process of cachaça proved to be an excellent environment for natural selection of yeasts with potential in the brewing industry. In the second objective of the present work, obtaining hybrids between S. cerevisiae and S. kudriavzevii by spontaneous crossing resulted in strains with improved characteristics compared to the parental ones. In total, 19 hybrids were obtained for the production of beer, cachaça and wine. Some of the hybrids showed better fermentation profiles, higher glycerol and ethanol production and increased production of aromatic compounds (esters and higher alcohols). The two methodologies applied to search for strains with potential for the production of beer, cachaça and wine were efficient for the selection of isolates that showed adequate performance for the production of beverages.